Friends, academic achievement, and school engagement during adolescence: A social network approach to peer influence and selection effects. (December 2018) - Wang, Ming-Te; Kiuru, Noona; Degol, Jessica L.; Salmela-Aro, Katariina
Abstract: Peers become increasingly important socializing agents for academic behaviors and attitudes during adolescence. This study investigated peer influence and selection effects on adolescents' emotional (i.e., flow in schoolwork, school burnout, school value), cognitive (i.e., school effort), and behavioral (i.e., truancy) engagement in school. A social network approach was used to examine students of post-comprehensive education in Finland ( N = 1419; mean age = 16). Students were asked to nominate peers to generate peer networks and to describe their own school engagement at two time points (one year apart). Network analyses revealed that the degree to which peer influence and selection effects occurred varied by dimension of school engagement. Over time, peers influenced students' emotional, cognitive, and behavioral engagement. Similarity in behavioral engagement, but not in emotional and cognitive engagement, increased the likelihood of forming new peer relationships. Additionally, some of the peer influence and selection effects on school engagement were moderated by student academic achievement. Highlights: Peer effect on school engagement includes influence and selection processes. School engagement is a multidimensional construct. Students had a tendency to choose new peers based on earlier similarity in behavioral engagement. Students became more similar to their peers in terms of emotional, cognitive, and behavioral engagement. Some peer influence and selection effects on engagement were moderated by achievement.